Implementation of Smart Contracts in TikTok Influencer Marketing - Sudadi Pranata; Fajrinoor Fanani; Dini Hidayati; Rosa Lesmana; Zinhle Ndlovu (IAIC Bangun Bangsa, 2025)
The rapid growth of TikTok as a social media platform has transformed influencer marketing, offering brands unparalleled opportunities to engage with their target audiences. However, issues such as lack of transparency, trust, and inefficiencies in payment processes remain significant challenges in influencer marketing, highlighting a critical GAP in both literature and practice. This study addresses these challenges by exploring the implementation of smart contracts, powered by blockchain technology, as a novel solution. Smart contracts provide an automated, secure, and transparent framework for managing influencer marketing campaigns. The research employs a quantitative approach with Structural Equation Modeling (SEM) as the primary methode, utilizing the SmartPLS tool. Data were collected from 200 respondents who are active TikTok users and have engaged with influencer marketing campaigns. The findings reveal that credibility, informativeness, and entertainment positively affect advertising value, while irritation negatively impacts it. Furthermore, advertising value significantly influences advertising attitude, which, in turn, impacts purchase intention. Additionally, advertising attitude moderates the relationship between advertising value and purchase intention, strengthening its effect. These results and conclusions emphasize the transformative potential of smart contracts in enhancing transparency, trust, and efficiency within influencer marketing. By introducing blockchain-based solutions, this study makes a significant novelty contribution to the literature, offering practical insights for brands and marketers. Specifically, smart contracts enable brands to ensure fair compensation, accurate performance measurement, and improved campaign outcomes. This study underscores the importance of leveraging cutting edge technologies to address existing gaps in influencer marketing, ultimately paving the way for more effective and transaction.